Pengaruh Celebrity Endorser Agnes Monica Terhadap Persepsi Dan Minat Beli Konsumen Produk Fresh Care - Bahaswan, Hana, Ahmad Mardalis, S.E., M.B.A (2015)
The purpose of this study was to examine the influence of celebrity endorser Agnes Monica to perception and consumer buying interest Fresh Care products. This study is a survey research with a quantitative approach. Sample collection techniques are non-probability samples using a sample of 100. The data collection methods used in this research using primary data. The analysis tool used is multiple linear regression analysis previously conducted test instruments and test hypotheses. The results of this study indicate that the variable perception of advertising, brand perception and purchase interest exist simultaneously positive influence and significant to celebrity endorser credibility variable. Effect of adjustedR2 in this study was 86% while the remaining 14% are influenced by other factor.